Case Report: Concomitant Massive Cerebral Venous Thrombosis and Internal Iliac Vein Thrombosis Related to Paucisymptomatic COVID-19 Infection - Beretta, Simone; Da Re, Fulvio; Francioni, Valentina; Remida, Paolo; Storti, Benedetta; Fumagalli, Lorenzo; Piatti, Maria Luisa; Santoro, Patrizia; Cereda, Diletta; Cutellè, Claudia; Pirro, Fiammetta; Montisano, Danilo Antonio; et al. (Frontiers in Neurology, 2021)
Thrombotic complications are common in COVID-19 patients, but cerebral venous system involvement, timing after infection, optimal treatment, and long-term outcome are uncertain. We report a case of massive cerebral venous thrombosis and concomitant internal iliac vein thrombosis occurring in the late phase of paucisymptomatic COVID-19 infection. Mild respiratory symptoms, without fever, started 3 weeks before headache and acute neurological deficits. The patient had silent hypoxemia and typical COVID-19 associated interstitial pneumonia. Brain CT scan showed a left parietal hypodense lesion with associated sulcal subarachnoid hemorrhage. CT cerebral venography showed a massive cerebral venous thrombosis involving the right transverse sinus, the right jugular bulb, the superior sagittal sinus, the straight sinus, the vein of Galen, and both internal cerebral veins. Abdominal CT scan showed no malignancy but revealed an asymptomatic right internal iliac vein thrombosis. Both cerebral venous thrombosis and pelvic vein thrombosis were effectively treated with unfractionated heparin started on the day of admission, then shifted to low molecular weight heparin, with a favorable clinical course. Nasopharyngel swab, repeated twice, tested negative for SARS-CoV-2. Serological tests confirmed SARS-CoV-2 infection. Our case supports active surveillance and prevention of thrombotic complications associated with COVID-19, which may affect both peripheral and cerebral venous system. Early initiation of unfractionated heparin may lead to good neurologic outcome.